Nursing diagnoses in hospitalized patients with COVID-19 in Indonesia - Nur Hidayati (Belitung Raya Foundation, 2021)
Background: The COVID-19 pandemic has become a global public health issue, and the roles of nurses are very much needed in providing nursing services in the current situation. The enforcement of appropriate nursing diagnoses for patients with COVID-19 is also fundamental in determining proper nursing care to help the patients achieve maximum health.